The Bank’s Financially Stable Supply Chain as the Basis for Attraction of Investors - Mariya S. Kazaeva; Gulnaz R. Sibaeva; Alexey G. Isavnin; Anton N. Karamyshev (International Journal of Supply Chain Management, 2018)
In this article the authors is examined a key conceptual apparatus and basis indicators of evaluation of the financial stability of supply chain in banks, methods of evaluation of financial stability of banks, through which potential investors can improve the process of making a decision about the rationality of cooperation with a financial institution and investing funds in this financial institution. Revealed main advantages and disadvantages of the suggested in this article method of analysis of banks financial stability of supply chain and formed a conclusion. In this article the authors formed the key purposes of carrying out the analysis of financial stability of commercial banks, introduced the formulas for calculating the crucial coefficients of appraisal of supply chain financial stability and indicated their interpretation, described their advantages and drawbacks, also described automated application programs for evaluating the financial status of commercial banks, allowing you to visually see and assess the current situation in which the financial institution is located, and also allows you to make a forecast of development trends, through which it is possible to identify and how reliable, competitive, and therefore the banks financially stable supply chain, which is mainly attractive for potential investors